Pulmonary adaptations to swim and inspiratory muscle training - Mickleborough, T. D.; Stager, J. M.; Chatham, K.; Lindley, M. R.; Ionescu, A. A. (European Journal of Applied Physiology, 2008)
Because the anomalous respiratory characteristics of competitive swimmers have been suggested to be due to inspiratory muscle work, the respiratory muscle and pulmonary function of 30 competitively trained swimmers was assessed at the beginning and end of an intensive 12-week swim training (ST) program. Swimmers (n = 10) combined ST with either inspiratory muscle training (IMT) set at 80% sustained maximal inspiratory pressure (SMIP) with progressively increased work-rest ratios until task failure for 3-days per week (ST + IMT) or ST with sham-IMT (ST + SHAM-IMT, n = 10), or acted as controls (ST only, ST, n = 10). Measures of respiratory and pulmonary function were assessed at the beginning and end of the 12 week study period. There were no significant differences (P > 0.05) in respiratory and pulmonary function between groups (ST + IMT, ST + SHAM-IMT and ST) at baseline and at the end of the 12 week study period. However, within all groups significant increases (P < 0.05) were observed in a number of respiratory and pulmonary function variables at the end of the 12 week study, such as maximal inspiratory and expiratory pressure, inspiratory power output, forced vital capacity, forced expiratory and inspiratory volume in 1-s, total lung capacity and diffusion capacity of the lung. This study has demonstrated that there are no appreciable differences in terms of respiratory changes between elite swimmers undergoing a competitive ST program and those undergoing respiratory muscle training using the flow-resistive IMT device employed in the present study; as yet, the causal mechanisms involved are undefined.